Environmental isotope 18 O in coastal karst spring waters as a possible predictor of marine microbial pollution - Mance, Diana (Array, 2018)
We tested the validity of the traditional hypothesis of a causal effect between rainfall occurrence, groundwater discharging into the sea, and marine microbial contamination. For groundwater characterization, we used the \( 18 O\) isotope. This stable isotope, together with 2 H, proved to be a useful physical, naturally occurring tracer primarily due to its abundance variations at different stages of water cycle. Test locations include Bakar Bay and selected adjacent Rijeka city beaches (Croatia). To test for statistical associations, we used the Panel Data Pairwise Granger Causality test. At examined locations, we found statistically significant relationships between the amount of rainfall and the abundance of \( 18 O\) isotope in groundwater, as well as relationships between the abundance of \( 18 O\) isotope in groundwater and faecal bacteria concentrations. Accordingly, \( 18 O\) isotope, when used as an indicator for the functioning of karstic groundwater systems, may also be used as the predictor of faecal contamination of bathing waters in associated karst littoral areas. We believe this physical method could be a valuable addition to present methods of predicting microbiological contamination and economic allocation of stock and flow pollutants in scarce common pool resources as fresh water basins, springs and beaches.